Assessment of groundwater quality in unconsolidated sedimentary coastal aquifer in Lagos State, Nigeria (2009)
This study assesses the quality of ground water from nine different borehole locations in Lagos State, Nigeria. Borehole water samples were carefully collected for physico - chemical analyses. Calcium, magnesium, iron, zinc, copper, manganese, aluminium, and silver, Nitrate, phosphate, fluoride, chloride, pH, conductivity, total dissolved solid, total suspended solid, hardness, summation of ions as well as the temperature and colour were assessed among the entire samples collected. The results show that: temperature ranges from 26.6 - 27.8°C, pH (7.27), average conductivity (462.2 ps/cm), TDS (204.73 mg/l), Total hardness (18.48 - 297.70 mg/l) and Chloride concentration (343.3 mg/l). However, a high value of chloride, 343.3 mg/l, was recorded in one of the water sample collected but, this is higher and above the limit of WHO guidelines of portable water (250 mg/i). This may be due to the proximity of the area where the sample was collected to the sea. Five samples of the water are is soft, that is, hardness was within a range of 0 - 75 mg/l recommended for safe drinking water, one is moderately hard while three samples are hard. Also, the presence of metals such as zinc, manganese, sodium, copper and magnesium were also observed. Results show that not all the water samples are safe for drinking purposes.